Pengembangan Pedoman E-Modul Berorientasi Student Active Learning Sebagai Pendukung Pembelajaran di Sekolah Dasar - Kuncahyono; Aini, Dian Fitri Nur (Universitas Nusantara PGRI Kediri, 2020)
This study aims to (1) produce a valid e-module guidelines for active student learning in elementary schools that are valid; (2) produce eligibility guidelines for student active learning oriented e-modules in Elementary Schools, and (3) produce practical student learning oriented e-module guidelines. This research uses ADDIE model development research design which consists of 5 levels, namely analysis, design, development, application, and evaluation. The results showed that the results of the validation trial of teaching materials experts and material experts, the average score obtained was 83.95 with valid criteria. The results of user trials (teachers and students) then the average score obtained is 3.5 very well / very practical